To the collector belong the spoils : modernism and the art of appropriation - Pfeifer, Annie (Ithaca : Cornell University Press, 2023)
"Rethinks collecting as an artistic, revolutionary, and appropriative modernist practice that flourishes beyond institutions like museums or archives and examines the relationship between literary modernism and twentieth-century practices of collecting objects through three author-collectors, Walter Benjamin, Carl Einstein, and Henry James"--
Introduction: Dangerous Passions -- "Morceaux de musée": James's Human Bibelots -- Sardanapalus's Hoard -- The Collector in a Collectivist State -- Trash-Talking in The Arcades Project -- The Collector and His Circle -- Dilettante of Wonder: Einstein and Documents -- Epilogue: Hoarding in a Digital Age.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on January 23, 2023).
JSTOR
Keywords: Benjamin, Walter, -- 1892-1940 -- Criticism and interpretation; Einstein, Carl, -- 1885-1940 -- Criticism and interpretation; James, Henry, -- 1843-1916 -- Criticism and interpretation; Benjamin, Walter, -- 1892-1940; Einstein, Carl, -- 1885-1940; James, Henry, -- 1843-1916; Collectors and collecting -- Philosophy; Modernism (Literature) -- History -- 20th century; LITERARY CRITICISM / Modern / General .; Collectors and collecting -- Philosophy; Modernism (Literature); Lifestyle, hobbies & leisure; Hobbies and Games; 1900-1999; Electronic books; Criticism, interpretation, etc; History